PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBASIS STEAM UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KITIS MURID - Novianti Dwi Rahmawati; Hasan Subekti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical thinking skills are essential 21st-century competencies that students must master. The 2022 PISA results show that Indonesia's science score (366) is below the OECD average, indicating low critical thinking skills among students. This study aims to describe: (1) the implementation of the STEAM-based guided inquiry model, (2) the improvement of students' critical thinking skills, and (3) student responses. The study used a descriptive quantitative approach with a one-group pretest-posttest design. The study was conducted at SMP Negeri 20 Surabaya in class VII G with 33 students. Data collection techniques included observation sheets, critical thinking tests (pretest and posttest), and response questionnaires. Data analysis included implementation percentage, Shapiro-Wilk normality test, Wilcoxon test, N-Gain Score, and mode analysis. The results show: (1) 100% implementation in the Very Good category; (2) a significant increase in critical thinking skills based on the Wilcoxon test (Z = −5.036; Sig. = 0.000 < 0.05) and an average N-Gain of 0.85 in the High category, with details per indicator: concluding (0.90), building basic skills (0.86), and giving simple explanations (0.77); and (3) 90% of student responses in the Very Good category. It is concluded that the STEAM-based guided inquiry model is effective in improving the critical thinking skills of junior high school students.